2022
DOI: 10.2147/nss.s326818
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study and Genetic Correlation Scan Provide Insights into Its Genetic Architecture of Sleep Health Score in the UK Biobank Cohort

Abstract: Most previous genetic studies of sleep behaviors were conducted individually, without comprehensive consideration of the complexity of various sleep behaviors. Our aim is to identify the genetic architecture and potential biomarker of the sleep health score, which more powerfully represents overall sleep traits. Patients and Methods: We conducted a genome-wide association study (GWAS) of sleep health score (overall assessment of sleep duration, snoring, insomnia, chronotype, and daytime dozing) using 336,463 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
2
7
0
Order By: Relevance
“…In the UK Biobank, significant genetic correlations were noted between a sleep health score composed of measures of sleep duration, snoring, insomnia, chronotype, and daytime dozing with 4 psychiatric disorders (major depressive disorder, attention deficit/hyperactivity disorder, schizophrenia, and autism spectrum disorder) and 9 plasma proteins, including cytochrome c oxidase. 32 Elevated cytochrome c oxidase levels were associated with long-term sleep deprivation in rats. 33…”
Section: Sleepmentioning
confidence: 99%
“…In the UK Biobank, significant genetic correlations were noted between a sleep health score composed of measures of sleep duration, snoring, insomnia, chronotype, and daytime dozing with 4 psychiatric disorders (major depressive disorder, attention deficit/hyperactivity disorder, schizophrenia, and autism spectrum disorder) and 9 plasma proteins, including cytochrome c oxidase. 32 Elevated cytochrome c oxidase levels were associated with long-term sleep deprivation in rats. 33…”
Section: Sleepmentioning
confidence: 99%
“…FUMA was used to annotate the genome-wide significant (GWS) risk loci (p<5e-8), lead independent SNPs (r 2 <0.1), and all SNPs in LD with independent SNPs (r 2 >=0.6) within a genomic region (including ANNOVAR functional consequence, CADD score, RegulomeDB score, as well as 15 chromatin states, and GWAS Catalog associations). We compared the GWS loci to loci reported by biobank-based GWAS of sleep traits published by June 2022, including insomnia 8,9 , sleep duration 7 , daytime sleepiness 10 , chronotype 12 , snoring 11 , daytime napping 60 , obstructive sleep apnea (OSA) 61 , restless legs syndrome (RLS) 62 , and prior SHS-ADD in UKB unrelated individuals 13 . GWS loci at least 500kb from any of the reported loci were noted as unreported.…”
Section: Methodsmentioning
confidence: 99%
“…For the UK Biobank additive sleep health score (SHS-ADD), consistent with previous studies 13,14 we assigned one point to each of five positive sleep traits, as follows: Chronotype: More a 'morning' than an 'evening' person or Definitely a 'morning' person; Sleep Duration: from 7 to 8 hours (inclusive); Insomnia Symptoms: Never/rarely; Snoring: No; Subjective daytime sleepiness: 0. Never/rarely.…”
Section: Sleep Health Score Constructionmentioning
confidence: 99%
“…Sleep is a complex behavior regulated in part by environmental and genetic factors [10,11]. Recent genome-wide association studies (GWAS) have identified genetic variants robustly associated with composite sleep [12][13][14], enabling the computation of Polygenic Scores (PRS) (predictors of genetic susceptibility to traits or diseases) of multidimensional sleep [15]. Combining PRS with phenotypic risk factors could help elucidate the interplay between genetic and environmental influences on disease risk [16,17].…”
Section: Introductionmentioning
confidence: 99%